Mirzo Ulug’bekning “To’rt ulus tarixi” asarida Chingizxon va mo’g’ul shaxzodalar bayoni - Usmanaliyeva Muqaddas (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, Mirzo Ulugbek's "History of Four Nations" contains information about the territories conquered by Sahibqiron Genghis Khan and his descendants, and comments are made. Information about the coming to the throne of the Mongol rulers and their policies is presented.